(3GdJLGQI GdGdcJQhfjI h MeGjJgG GdbGfhfjIs - (3YHO GdaJGM Hjhej(B, (3MLGRjs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2006)
(3JWhQ GdJLGQI GdGdjcJQhfjI h GdJYQja HgG , MLe gPg GdJLGQI h fabGJgG GdHGgVI , GdJcfhdhLjG h GfJbGdgG Hjf Ohd GdYGde h GNJQGb ehGbY GdJLGQI GdGjdjcJQhfjI h GJdGagG Ch JOejQgG , eTcdGJ COGA GdhaGA , HWGbGJ GdGFJeGf , GdeSJgdc h MeGjJg aj GdJLGQI GdGjdjcJQhfjI , GdbGfhf GdhGLH GdJWHjb h GdeMceI GdeNJUI , MeGjI GdJhbjY GdGdcJQhfj , JTajQ GdHjGfGJ h MeGjI GdeSJgdc , MeGjI CSeGA GdOhejf h GdYdGeGJ GdJLGQjI , eaghe GdeUdMI GdeMejI h GdeHGOF GdJj JMcegG , MeGjI GdeUdMI VO GdZT h GdJMGjd , GdONhd ZjQ GdeTQhY dehGbY GdJLGQI GdGdjcJQhfjI , GdMeGjI GdLfGFjI ddHjGfGJ GdTNUjI Ch GdGSejI , GdeSDhdjI GdLfGFjI debOej GdNOeGJ GdhSjWjI aj GdGfJQfjJ , MeGjI GdGehGd aj fWGb GdJLGQI GdGjdjcJQhfjI , GdJYGed aj HjGfGJ GdJLGQI GdGdjcJQhfjI HOhf JQNjU h GfJgGc SQjI h NUhUjI GdHjGfGJ , LQjeI GdJUQjM YeOG HeYWjGJ NGWFI , LQGFe GdGYJOGA Ydi GdJhbjY GdGdjcJQhfj h LQGFe GdGYJOGA Ydi GdHjGfGJ GdeTaQI , GSJZdGd GdeJYGed aj GdHjY GdGdcJQhfj , LQjeI GdJgQH GdVQjHj aj GdJLGQI GdGdcJQhfjI h MeGjI GdHWGbGJ GdeeZfWI chSjdI haGA aj GdJLGQI GdGdjcJQhfjI , GdMeGjI GdLfGFjI ddJLGQI GdGdjcJQhfjI aj aQfSG h aj dcSeHhQL h aj GdJTQjY GdeUQj h aj GdbGfhf GdJhfSj(B.s
Keywords: (3GdJLGQIs; (3GdJLGQI GdEdcJQhfjIs; (3GdbGfhf GdJLGQjs